Results of a pilot clinical trial of the safety and efficacy of an original glycoprotein IIb/IIIa receptor inhibitor in acute coronary syndrome - S. V. Lukyanov; Yu. F. Glukhov; E. V. T.; B. M. Tankhilevich; D. A. Zateyshchikov; T. V. Khlevchuk; I. B. Bondareva (Кардиоваскулярная терапия и профилактика, 2023)
Aim. To study the safety and efficacy of Angipure in acute ST-segment elevation coronary syndrome (STE-ACS) and high-risk percutaneous transluminal coronary angioplasty (PTCA) compared with eptifibatide.Material and methods. The study included 157 patients with STE-ACS. High-risk PTCA included massive or total coronary artery thrombosis, noreflow/slow-reflow phenomenon, and acute stent thrombosis. Fifty-five people received Angipure at a dose of 0,72 mg/kg, 52 — at a dose of 0,40 mg/kg, while 50 patients received eptifibatide (Integrilin). We conducted clinical and laboratory studies, electrocardiography (ECG), coronary angiography.Results. According to the criteria "Frequency and severity of hemorrhagic events, including hemorrhagic stroke", "Frequency, severity of other adverse events", there were no differences in safety between Angipure at doses of 0,40 and 0,72 mg/kg and eptifibatide. Complaints, clinical symptoms, vital signs, complete blood count, biochemical and coagulation tests, ECG in patients of different groups were similar and had unidirectional dynamics. The use of Angipure or eptifibatide was considered effective if no adverse outcomes (death, recurrent acute ischemic event, need for urgent revascularization) were observed within 30 days. There were no lethal outcomes. One repeated acute ischemic event was registered in each group. In groups of patients receiving Angipure 0,40 mg/kg and eptifibatide, urgent revascularization was required once each.Conclusion. Angipure and eptifibatide have similar safety and efficacy.